Histone H3 Variants in Trichomonas vaginalis - Zubácová, Zuzana; Hostomská, Jitka; Tachezy, Jan (Eukaryotic cell, 2012)
The parabasalid protist Trichomonas vaginalis is a widespread parasite that affects humans, frequently causing vaginitis in infected women. Trichomonad mitosis is marked by the persistence of the nuclear membrane and the presence of an asymmetric extranuclear spindle with no obvious direct connection to the chromosomes. No centromeric markers have been described in T. vaginalis, which has prevented a detailed analysis of mitotic events in this organism. In other eukaryotes, nucleosomes of centromeric chromatin contain the histone H3 variant CenH3. The principal aim of this work was to identify a CenH3 homolog in T. vaginalis. We performed a screen of the T. vaginalis genome to retrieve sequences of canonical and variant H3 histones. Three variant histone H3 proteins were identified, and the subcellular localization of their epitope-tagged variants was determined. The localization of the variant TVAG_185390 could not be distinguished from that of the canonical H3 histone. The sequence of the variant TVAG_087830 closely resembled that of histone H3. The tagged protein colocalized with sites of active transcription, indicating that the variant TVAG_087830 represented H3.3 in T. vaginalis. The third H3 variant (TVAG_224460) was localized to 6 or 12 distinct spots at the periphery of the nucleus, corresponding to the number of chromosomes in G(1) phase and G(2) phase, respectively. We propose that this variant represents the centromeric marker CenH3 and thus can be employed as a tool to study mitosis in T. vaginalis. Furthermore, we suggest that the peripheral distribution of CenH3 within the nucleus results from the association of centromeres with the nuclear envelope throughout the cell cycle.
Keywords: buněčné jádro; Trichomonas vaginalis; mitóza; Molecular Sequence Data; G1 fáze; Centromere; Histones; Cell Nucleus; genom protozoální; Chromosomes; Nucleosomes; aktivace transkripce; protozoální proteiny; histony; sekvenční analýza proteinů; centromera; Sequence Analysis, Protein; Mitosis; Nuclear Envelope; Transcriptional Activation; sekvence aminokyselin; transformace genetická; chromozomy; Transformation, Genetic; G1 Phase; Microscopy, Fluorescence; jaderný obal; molekulární sekvence - údaje; Genome, Protozoan; G2 Phase; Protozoan Proteins; Amino Acid Sequence; nukleozomy; fluorescenční mikroskopie; G2 fáze